Analysis and design of the biasing network for 1 GHz bandwidth RF power amplifier - Md. Golam Sadeque; Zubaida Yusoff; Mardeni Roslee; Shaiful Jahari Hashim; Azah Syafiah Mohd Marzuki (Institute of Advanced Engineering and Science, 2021)
The bandwidth of the wireless communication has increased due to the various applications of the wireless devices. A radio frequency power amplifier (RFPA) is one of the crucial components of the transceiver. So, to meet the requirement of the bandwidth, wideband RFPA is needed. The RFPA not only requires a wideband matching network but importantly the biasing network. For the next-generation communication system, a wideband biasing network is needed to operate in the wide GHz bandwidth range. In this paper, a wideband biasing network for the power amplifier is designed using a quarter-wave transmission line and a butterfly stub for the frequency band of 3.3 GHz to 4.3 GHz. Roger’s RO3006 is used as the substrate for the design of the biasing network. The designed network performed well in the required frequency range. The performances of the biasing network have shown 9 dB to 19 dB return loss, the radio frequency (RF) isolation has more than 35 dB, and 0 dB to 1.5 dB insertion loss. This wideband biasing network can be used for the next generation communication system.